PENGARUH BAHASA SEDERHANA TERHADAP PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI KELOMPOK B TK DAMA KUMARA - I Made Hartawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
Education in kindergarten is basically simple and concrete learning and children will get direct experience. Group B children in kindergarten aged 5-6 years have a very strong curiosity, so the learning outcomes they get need to be developed optimally in order to develop in a positive direction. One of the early childhood development that affects learning outcomes is language development activities. Every early childhood life, always have difficulty with the language they use. Because every language that comes out of their mouth, not necessarily they will understand the meaning. Especially in kindergarten, this simple language learning has a positive effect on children's cognitive development. This research is clarified as correlational research. The population of this study were all students in group B whose ages ranged from 5 to 6 years with a total of 30 children. The data source comes from primary and secondary data. The data analysis method used was chi-square analysis. The results of the Chi-square data analysis showed the data results of 9.22. Thus the null hypothesis is rejected and the working hypothesis is accepted, which means there is an effect of simple language on cognitive development in early childhood group B TK Dama Kumara. If seen from the significant value of 5 percent (3.84), while the analysis value is 9.22, it can be believed that the influence of learning with cognitive abilities is strong. Thus it can be concluded that the development of simple language (speaking) on cognitive learning outcomes (hearing) greatly influences the cognitive development of children at TK Dama Kumara.Keywords: Simple language, Cognitive.